[Letter to TAN members on No-Smoking Bill] - SCANLAN,RE (Tufts Archival Research Center, 2007)
Letter to members of Tobacco Action Network, urging them to work against the New York State No-Smoking in Public Places Bill. Asks members to write to State Representatives. Provides quotes from allied organizations, questions and answers about proposed legislation, and list of coalition members. Iterates economic burden, impractical nature, and unfairness of proposal.